2010
DOI: 10.1152/ajpheart.00316.2009
|View full text |Cite
|
Sign up to set email alerts
|

Nonanticoagulant heparin reduces myocyte Na+and Ca2+loading during simulated ischemia and decreases reperfusion injury

Abstract: Heparin desulfated at the 2-O and 3-O positions (ODSH) decreases canine myocardial reperfusion injury. We hypothesized that this occurs from effects on ion channels rather than solely from anti-inflammatory activities, as previously proposed. We studied closed-chest pigs with balloon left anterior descending coronary artery occlusion (75-min) and reperfusion (3-h). ODSH effects on [Na(+)](i) (Na Green) and [Ca(2+)](i) (Fluo-3) were measured by flow cytometry in rabbit ventricular myocytes after 45-min of simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…19 Focused attempts to include modified terms related to diabetes mellitus or preoperative blood sugar levels could not significantly improve the ability to predict the risk of MCCs or improve the accuracy or the discrimination of the index. Glycosylated hemoglobin has been advocated as an important risk factor in diabetic outcomes and may be a factor that could potentially improve the index; [20][21][22] however, the data in our database were insufficient to assess this variable. In our view, it would be important to drop the diabetes terminology from the RCRI; inclusion has the potential to create patient safety issues.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…19 Focused attempts to include modified terms related to diabetes mellitus or preoperative blood sugar levels could not significantly improve the ability to predict the risk of MCCs or improve the accuracy or the discrimination of the index. Glycosylated hemoglobin has been advocated as an important risk factor in diabetic outcomes and may be a factor that could potentially improve the index; [20][21][22] however, the data in our database were insufficient to assess this variable. In our view, it would be important to drop the diabetes terminology from the RCRI; inclusion has the potential to create patient safety issues.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, troponin was measured more frequently in patients with elevated RCRI scores, and we have previously documented and shown that this clinically based measurement can deliver up to a threefold underestimation of the rate of myocardial damage. 20 In conclusion, the four validated terms from the original RCRI (i.e., high-risk type of surgery, history of ischemic heart disease, history of congestive heart failure, and history of cerebrovascular disease) should continue to be used to estimate risk and allocate resources in elective surgical patients. The elimination of diabetes from the index would have little effect on the performance of the ''index'' except to move more patients to a lower risk category.…”
Section: Limitationsmentioning
confidence: 99%
“…Adult mouse ventricular myocytes were isolated as previously described on laminin-coated chambers (4,51). After superfusion in a normoxic solution (pO 2 ϭ 580 Ϯ 2.0 mmHg), cells were bathed in an ischemic solution (pO2 ϭ 20.5 Ϯ 3.5 mmHg) for 5 min (8).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many studies show that RAN inhibits I Na.L under pathological conditions and thus alleviates Ca 2+ overload and cell damage (37, 41 -45). In addition, RAN remarkably attenuates ischemia-induced myocardial diastolic Ca 2+ overload, improves left ventricular function during isch- emia/reperfusion, and protects cardiac cells from necrosis (12,17,18,22,27,34,40,46). However, to our knowledge, the effect of RAN on hypoxia-increased I Na.L has not been studied to date.…”
Section: Discussionmentioning
confidence: 76%